Anaesthesia and deep brain stimulation - Bindu, Barkha; Bithal, Parmod K. (Journal of Neuroanaesthesiology and Critical Care, 2016)
Deep brain stimulation (DBS) is becoming an increasingly popular minimally invasive surgical procedure for various movement disorders, especially Parkinson’s disease. Different nuclei have been identified depending on patients’ symptoms, but the success or failure of the procedure depends on various other factors such as proper patient selection and risk-benefit analysis. While various techniques of anaesthesia including monitored anaesthesia care, conscious sedation and general anaesthesia are being used routinely, no clear-cut evidence exists as to the best technique for this procedure. This review article discusses the surgical procedure of DBS, devices currently available, perioperative anaesthetic concerns and techniques, effect of anaesthetic drugs on microelectrode recordings and macro-stimulation and associated complications.
Keywords: Anaesthesia; deep brain stimulation; Parkinson’s disease